Occurrences of the National Identification Issues in the Kazakhstan Press in the late-Soviet period - Sadykov С. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2018)
The unsolved problems which existed due to different objective and subjective factors had led to the loss of economic development rates and troubles by the mid-1980s in the USSR. Social stagnation of the system identified that the country was on the eve of the crisis. The neglect of the government to the identity of the nation and many issues concerning the development of the country made people anxious about their authorities. This made the situation complicated and dangerous. Despite the aggravation of interethnic relations in the country, there were facts that concealed real problems and truth in this sphere. It was known that far-fetched schemes were not suitable for the life flow. It was under the pressure in the years of reconstruction.